Responsivity of serotonin transporter knockout rats to short and long access to cocaine: Modulation of the glutamate signalling in the nucleus accumbens shell. (8th March 2022) - Caffino, Lucia; Mottarlini, Francesca; Targa, Giorgia; Verheij, Michel M. M.; Fumagalli, Fabio; Homberg, Judith R.
Abstract : Background and Purpose: It has been well established that glutamate in the nucleus accumbens (NAc) plays a critical role in the motivation to take drugs of abuse. We have previously demonstrated that rats with ablation of the serotonin transporter (SERT −/− rats) show increased cocaine intake reminiscent of compulsivity. Experimental Approach: By comparing SERT −/− to SERT +/+ rats, we investigated whether SERT deletion influences glutamate homeostasis under control conditions as well as after short access (ShA: 1 h per session) or long access (LgA: 6 h per session) to cocaine self‐administration. Rats were killed at 24 h after the last self‐administration session for ex vivo molecular analyses of the main determinants of the glutamate system, including transporters (vesicular and glial), receptors (main post‐synaptic subunits of NMDA and AMPA receptors together with the metabotropic subunit mGLUR5), and scaffolding proteins (SAP102, SAP97, and GRIP) in the NAc shell (sNAc) Key Results: In cocaine‐naive animals, SERT deletion was associated with changes indicative for a reduction in glutamate signalling. ShA and LgA exposure led to a further dysregulation of the glutamatergic synapse. Conclusion: SERT deletion may render the glutamatergic synapses of the NAc shell more responsive to both ShA and LgA intake of cocaine. Abstract :